Literature Review: An Analysis of the Effectiveness of Career Readiness of High School Students Using Super Life Span Theory - Ernawati Sinaga, Rike; Daharnis; Ifdil (Yana Research, 2025)
Career readiness of high school students is an important aspect that needs attention, especially because they are in the transition period to higher education or the world of work. This study aims to analyze the effectiveness of Super Life Span theory in supporting high school students' career readiness through a literature review approach. Super Life Span theory offers a comprehensive framework for understanding individual career development throughout life, with a focus on self-concept and stages of exploration. This review collects and analyzes the results of various studies related to the application of Super theory in career guidance services. The results of the analysis show that the implementation of Super Life Span theory is effective in helping students recognize their potential, interests, and personal values. Career guidance services based on this theory are also proven to support more mature and purposeful career decision-making through a structured service program, including personality assessment, career information provision, and individual needs-based planning. In addition, Super theory shows flexibility in being applied to modern career contexts, such as creative and technology-based industries. The conclusion of this study confirms that Super Life Span theory is a relevant and effective approach to enhance high school students' career readiness. The theory not only helps students understand their career development but also provides a practical framework for counselors in designing more adaptive and strategic career guidance services.